Factors Associated with Cervical Cancer Screening and Prevalence of Premalignant Cervical Lesions in a Rural Setting in Cameroon: a Cross-Sectional Analytical Study: Cervical cancer screening and prevalence of premalignant lesions - Mforteh Achuo Ascensius Ambe; Dohbit Sama Julius; Boten Merlin; Takang William Ako; Pisoh Dobgima Walters; Ebai Clinton Tiku; Tchoufack Brice Akwokezeh Afuh; Tameh Theodore Yangsi; Afungchwi Glenn Mbah; Mbu Robinson Enow (HEALTH RESEARCH IN AFRICA, 2023)
Despite being preventable through vaccination against Human Papilloma virus and screening, cervical cancer still presents with a high burden in low- and middle-income countries. The aim of this study was to determine factors associated with cervical cancer screening and prevalence of cervical premalignant lesions in a rural community in Cameroon. Methods. Community-based cross-sectional study using secondary data collected in a health campaign to create awareness and offer free screening to the population. Sociodemographic data, data on knowledge of prevention of cervical cancer, and past history of screening were collected. The R software version 4.2.2. was used for statistical analysis. Results. A total of 476 participants were enrolled. Over 32% of the population had heard of cervical cancer, 12.8% had heard of HPV infection, 7.1% knew a vaccine exists, 27.5% knew of screening, and 23.5% had heard of early treatment of lesions. Previous health education on cervical cancer (aOR:230, 95% CI: 55-969, p<0.0001), attending a cervical cancer screening health campaign (aOR: 23, 95% CI: 2.15-246, p= 0.009), were significantly associated with cervical cancer screening. Conclusion. Cervical cancer screening in the rural area relies largely on opportunistic screening provided during health campaigns. Free health campaigns could therefore be a very useful strategy to improve awareness and the rate of screening for cervical cancer in rural communities.